Interior of a Church (16260530716) - Miami University... (Wikimedia Commons, 2015)
Carte postale ancienne issue de Wikimedia Commons. Titre: Interior of a Church (16260530716). Persistent URL: digital.lib.miamioh.edu/cdm/compoundobject/collection/pos... Subject: World War I | Lost architecture | Churches | France--Roye | miami digital collections | bowden postcard collection
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale